2016
DOI: 10.1007/s10103-016-2101-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the alendronate and irradiation with a light-emitting diode (LED) on murine osteoclastogenesis

Abstract: Photomodulation therapy (PBMT) using light-emitting diode (LED) has been proposed as an alternative to conventional osteoporosis therapies. Our aim was to determine the effect of irradiation with a light-emitting diode on receptor activator of NF-κB ligand (RANKL)-mediated differentiation of mouse bone marrow macrophages into osteoclasts and compare it to alendronate treatment. The cells were irradiated with LED at 635±10 nm, 9-cm spot size, 5 mW/cm, and 18 J for 60 min/day in a CO incubator. The differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Beyond its effects on osteoblasts, some studies have also demonstrated the potential of PBM to inhibit osteoclastogenesis [41,42]. Reduced ROS production has been proposed as a possible cause of reduced osteoclastogenesis following irradiation [4143].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its effects on osteoblasts, some studies have also demonstrated the potential of PBM to inhibit osteoclastogenesis [41,42]. Reduced ROS production has been proposed as a possible cause of reduced osteoclastogenesis following irradiation [4143].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its effects on osteoblasts, some studies have also demonstrated the potential of PBM to inhibit osteoclastogenesis [41,42]. Reduced ROS production has been proposed as a possible cause of reduced osteoclastogenesis following irradiation [4143]. Moreover, many studies found that PBM could promote bone healing and improve bone quantity and strength in ovariectomized rats [39,40,4446], in which near infrared light was more commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the primers used to target various genes are shown in Table . Details of the reaction system and amplification procedures have been described previously …”
Section: Methodsmentioning
confidence: 99%
“…Details of the reaction system and amplification procedures have been described previously. (24) Luciferase reporter assay BMSCs were transiently transfected with a Runx2 or OSX target sequence-linked luciferase reporter plasmid using Lipofectamine (Invitrogen), according to the manufacturer's instructions. After transfection, cells were incubated in the designated medium for 7 days.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Low-intensity light therapy, ordinarily referred to to as photombiomodulation (PBM) by light in the far-red to near-infrared (NIR) region of the spectrum (630-1000 nm), stimulates several cellular functions. PBM therapy has been shown to downregulate osteoclastogenesis, increase the cell proliferation including that of fibroblasts and to promote angiogenesis thus accelerating the bone repair process [1,2,16]. The use of light-emitting diodes (LEDs) and low level lasers (LLLs) are favourable therapeutic approaches in the treatment of infected and hypoxic wounds [17,18].…”
Section: Introductionmentioning
confidence: 99%